Study of geometrical features the surfaces of large-sized objects by measuring system with three phase light distance measuring devices - Бабак, В.П.; Шмаров, В.М.; Калита, В.М. (Proceedings of National Aviation University, 2004)
The theoretical description of measuring system with three phase measuring devices is carried out which allows during one measurement to determine rules of three points on a researched surface of a large-sized product. Is shown, that through such system it is possible to carry out restoration the surfaces of objects, which are considered as set of differently focused planes. Also is shown, that using the given measuring system, it is possible to carry out geometrical approximation the surfaces of objects as secant planes by limited of hexagon.